Efficiency and Market Share in Hungarian Corporate Sector - Gabor Korosi; Laszlo Halpern (Hungarian Academy of Sciences, Institute of Economics, 2000)
This paper investigates the link between competition and efficiency for the Hungarian corporate sector during various phases of the transition process. We employ frontier production functions to explore differences among groups of firms, and to identify the typical adjustment process of each group separately throughout the transition period until 1997. The estimated production functions indicate a gradual improvement in efficiency and a shift from decreasing to increasing returns to scale due to the growing share of small firms. Market share can be explained by domestic and foreign competition and by the efficiency of the firm.
Keywords: C23; D21; D24; 330; firm in transition economy; production functions; efficiency